1983
DOI: 10.1136/bmj.287.6389.384
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir prophylaxis against herpes virus infections in severely immunocompromised patients: randomised double blind trial.

Abstract: Twenty patients undergoing allogeneic bone marrow transplantation and 39 patients receiving remission induction chemotherapy for acute leukaemia were entered into a double blind, placebo controlled stratified trial of acyclovir prophylaxis against herpes group virus infections. Within the transplant group intravenous acyclovir 5 mg/kg twice daily given throughout the period of granulocytopenia completely prevented oropharyngeal herpes simplex virus infection compared with a 50% incidence in the placebo arm (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
57
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(58 citation statements)
references
References 0 publications
1
57
0
Order By: Relevance
“…T his study also contirms that both intravenous and oral acyclovir can significantly reduce the Months since transplant rate of infections with HSV after allogeneic bone marrow ---Control -6 Month ACV transplantation. This has been previously shown by others (Wade et al, 1984;Gluckman et al, 1983;Saral et al, 1981; Acyclovir prophylaxis study Hann et al, 1983;Shepp et al, 1987). Meyers et al (1988) have observed a reduction in CMV infection in patients given larger doses of acyclovir (500 mg m -2) compared to a concurrent, non-randomised, control group.…”
Section: Discussionsupporting
confidence: 62%
“…T his study also contirms that both intravenous and oral acyclovir can significantly reduce the Months since transplant rate of infections with HSV after allogeneic bone marrow ---Control -6 Month ACV transplantation. This has been previously shown by others (Wade et al, 1984;Gluckman et al, 1983;Saral et al, 1981; Acyclovir prophylaxis study Hann et al, 1983;Shepp et al, 1987). Meyers et al (1988) have observed a reduction in CMV infection in patients given larger doses of acyclovir (500 mg m -2) compared to a concurrent, non-randomised, control group.…”
Section: Discussionsupporting
confidence: 62%
“…More importantly they cause dysphagia leading to inadequate food and fluid intake in patients who are often very ill and have a high metabolic rate. They may also act as a portal of entry for micro-organisms causing secondary infections (Lundgren et al, 1985) which in turn may delay reconstitution of the bone marrow and hence prolong the period of neutropenia (Hann et al, 1983).…”
mentioning
confidence: 99%
“…In the past year eight of 25 (32%) patients with non-Hodgkin's lymphoma, admitted to our oncology ward with pyrexia when neutropenic, had virologically confirmed HSV infections. Intravenous acyclovir has been shown in randomised, placebo controlled trials to be effective in the treatment of HSV infection in immunocompromised patients (Chou et al, 1981;Mitchell et al, 1981;Wade et al, 1982), and in the prophylaxis of HSV infection (Hann et al, 1983;Saral et al 1981). A report of oral acyclovir prophylaxis in bone marrow transplant patients has shown a reduced incidence of HSV in those patients treated with acyclovir compared with placebo, without significant toxicity (Gluckman et al 1983).…”
mentioning
confidence: 99%